GR43175, a selective agonist for the 5-HT1-like receptor in dog isolated saphenous vein. - Humphrey, P. P. (1988)
1. We describe the actions of a novel and selective 5-HT1-like receptor agonist, GR43175, in a range of isolated tissue preparations containing different 5-hydroxytryptamine (5-HT) receptor types. 2. GR43175 was a potent agonist at 5-HT1-like receptors mediating contraction of the dog isolated saphenous vein and also at those inhibiting neuronally mediated contractions in the same preparations. For both actions, GR43175 was approximately four times weaker than 5-HT. 3. GR43175 was devoid of agonist properties at 5-HT1-like receptors mediating relaxation of the cat isolated saphenous vein. 4. GR43175 was devoid of agonist properties at 5-HT2 receptors mediating contraction of the rabbit isolated aorta, pig coronary artery, greyhound coronary artery and beagle femoral artery. 5. GR43175 was devoid of agonist properties at 5-HT3 receptors mediating depolarization of the rat isolated vagus nerve. 6. The contractile response to GR43175 in the dog isolated saphenous vein was selectively antagonized by methiothepin but was resistant to antagonism by the 5-HT2 receptor blocking drug ketanserin and the 5-HT3 receptor blocking drug MDL 72222. Methiothepin antagonized the contractile action of 5-HT and GR43175 to an equal extent suggesting that both agonists act at the same receptor. 7. The results demonstrate that GR43175 is a highly selective agonist for the 5-HT1-like receptors found in the dog saphenous vein. The absence of an action of GR43175 at 5-HT1-like receptors mediating relaxation of the cat isolated saphenous vein provides further evidence that 5-HT1-like receptors are heterogeneous.